Legal regulation for medically assisted reproduction in Argentina - Carlevaro, Agustín Sebastián (2020)
This paper analyzes the legal and political issues that women face on their own experience of being able or not to conceivingand their attributing to the domains of nature and technology. We use the Data Matrix model. The procedure involves the individual analysis of right holders, their benefits, the enforceability way to access to this right and the regulated entities in the Argentine Republic. These data was operationalized under legal, realistic and bibliographic methods. We conclude that the current Argentine legal system regulates the coverage of medically assisted reproduction techniques and their effects on public law. However, there are still some legal loopholes in private law regarding civil liability, affiliation, successions and specific obligations of the parts.